Enhanced Shelf Life of Chicken Fillets using an Active Pad Based on Alginate Hydrogel Containing a β-Cyclodextrin/Carvacrol Inclusion Complex - Guarda-Moraga, A; Bruna-Bugueno, J (Springer, 2026)
The use of inclusion complexes based on β-cyclodextrin (BCD) and essential oil derivatives, such as carvacrol (CARV), represents a promising strategy for the design of active packaging systems with antimicrobial properties, particularly in applications where controlled release of the active agent is required. In this context, the incorporation of inclusion complexes into alginate hydrogels is proposed as an effective approach for developing antimicrobial active pads suitable for the tray packaging of chicken meat because they can act simultaneously as exudate removers and generators of antimicrobial activity. Hence, active hydrogels composed of alginate and BCD/CARV inclusion complex were used to develop antibacterial pads intended for application in chicken packaging using a tray system under refrigerated conditions. To achieve this, active alginate hydrogels were prepared using calcium cation as a crosslinking agent, and different contents of the BCD/CARV inclusion complex (5 and 10% wt.). As a result, PAD/ALG-CI5 and PAD/ALG-CI10 were used as active alginate hydrogels, while PAD/ALG corresponded to the alginate hydrogel without the inclusion complex. On the other hand, the shelf life of chicken fillets packaged in a tray system with PAD/ALG, PAD/ALG-CI5, and PAD/ALG-CI10 was evaluated by monitoring pH, color, and total aerobic mesophilic bacteria (TAMB) counts over a 7-day storage period. Active pads did not affect the pH of the chicken and prevented color changes in the samples during storage. Additionally, microbiological results indicated that the shelf life of the chicken was extended by 1 or 2 days, depending on the inclusion complex content in the material. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2025.